Btk inhibitor ibrutinib reduces inflammatory myeloid cell responses in the lung during murine pneumococcal pneumonia - de Porto, Alexander P.; Liu, Zhe; de Beer, Regina; Florquin, Sandrine; de Boer, Onno J.; Hendriks, Rudi W.; van der Poll, Tom; de Vos, Alex F. (Molecular medicine (Cambridge, Mass.), 2019)
Background Streptococcus pneumoniae is a major causative agent in community-acquired pneumonia and sepsis. Overwhelming lung inflammation during pneumococcal pneumonia may hamper lung function. Ibrutinib is an irreversible inhibitor of Bruton’s tyrosine kinase (Btk), a key signaling protein controlling the activation of various immune cells, including macrophages and neutrophils. The aim of this study was to determine whether ibrutinib treatment ameliorates acute lung inflammation during pneumococcal pneumonia. Methods Mice were treated orally with ibrutinib and the effect on acute pulmonary inflammation elicited by the gram-positive bacterial cell wall component lipoteichoic acid (LTA) and during ceftriaxone-treated pneumococcal pneumonia was assessed. Results Treatment with ibrutinib prior to and after intranasal LTA instillation reduced alveolar macrophage activation, neutrophil influx, cytokine release and plasma leakage into the lung. Postponed treatment with ibrutinib supplementing antibiotic therapy during ongoing pneumococcal pneumonia did not impair bacterial killing in lung, blood and spleen. In this setting, ibrutinib reduced alveolar macrophage and systemic neutrophil activation and substantially diminished further monocyte and neutrophil influx in the lung. In vitro, ibrutinib inhibited macrophage TNF secretion and neutrophil activation upon LTA and pneumococcal stimulation. Conclusions Taken together, these data indicate that the Btk inhibitor ibrutinib reduces inflammatory myeloid cell responses during acute pulmonary inflammation evoked by LTA and antibiotic-treated pneumococcal pneumonia and suggest that ibrutinib has the potential to inhibit ongoing lung inflammation in an acute infectious setting.